Perancangan Perancangan Interkoneksi Pembangkit Listrik Tenaga Surya 1 MWp On-Grid Pada Jaringan Distribusi Cileungsi - Mariya JP (Sekolah Tinggi Teknik - PLN, 2019)
Bogor is one of the major cities in Indonesia where electricity demand is increasing rapidly every year. PT Sinar Energi Indonesia has large vacant land plans to build a 1 MW Solar Power Plant (SPP) in the Cileungsi area. This is supported by the location which is close to the Cileungsi substation owned by PLN (800 meters) and also SPP is suitable with the characteristics of the electricity load in the area where the peak load occurs during the day and the development of SPP will reduce pollution caused by thermal plants. Interconnection of SPP with Cileungsi substation requires separate analysis to determine the best interconnection design between SPP and PLN grid. The author will use ETAP 12.6 software for load flow, short circuit and transient analysis so that the interconnection design will not cause harm, both for developers and for PLN. From the simulation results with ETAP 12.6 software does not show a negative impact (small power losses, small voltage drop, and the value of the short circuit current that occurs does not exceed the capacity of the equipment), and if there is a disturbance in the SPP unit, the transient shows within 1 second, the system has stabilized. Beside technical side, the economic point of view from this Solar Power Plant will also have a positive impact with the planned electricity tariff value of 6,884 cent US / kWh, still below the local production cost value (West Java 6.91 cent US / kWh, ESDM Ministerial Decree No.55 years 2019). Therefore, this research is expected to be able to help the developer and PLN in interconnection of the Solar Power Plant Cileungsi to PLN grid.